Recent Advances in Genetic and Epigenetic Modulation of Animal Exposure to High Temperature - Wu, Jiong; Zhang, Weiwei; Li, Chenghua (Frontiers in Genetics, 2020)
Animals have evolved multiple systems, including genetic and epigenetic systems, to respond accordingly to heat exposure and heat acclimation. Heat exposure greatly affects immunity, changes metabolic processes, and poses a serious threat to animals. Heat acclimation is induced by repeated organism exposure to heat stress to dissipate heat. This review focuses on genetic modulation via heat shock transcription factors and calcium as two important factors and compares the changes of HSPs under heat stress and heat acclimation. Epigenetic regulation summarizes the role of HSPs in DNA methylation and histone modifications under heat stress and heat acclimation. These genetic and epigenetic modifications protect cells from thermal damage by mediating the transcriptional levels of heat-responsive genes. This review highlights recent advances in the genetic and epigenetic control of animal thermal responses and their interactions.